A cadaveric model to evaluate the effect of unloading the medial quadriceps on patellar tracking and patellofemoral joint pressure and stability - Stephen,J; Alva,A; Lumpaopong,P; Williams,A; Amis,AA (Journal of Experimental Orthopaedics, 2018)
BackgroundVastus Medialis Muscles (VMM) damage has been widely identified following patellar dislocation. Rehabilitation programmes have been suggested to strengthen the VMM and reduce clinical symptoms of pain and instability. This controlled laboratory study investigated the hypothesis that reduced Vastus Medialis Obliquus (VMO) and Vastus Medialis Longus (VML) muscle tension would alter patellar tracking, stability and PFJ contact pressures.MethodsNine fresh-frozen dissected cadaveric knees were mounted in a rig with the quadriceps and iliotibial band loaded to 205 N. An optical tracking system measured joint kinematics and pressure sensitive film between the patella and trochlea measured PFJ contact pressures. Measurements were repeated for three conditions: 1. With all quadriceps heads and iliotibial band (ITB) loaded; 2. as 1, but with the VMO muscle unloaded and 3. as 1, but with the VMO and VML unloaded. Measurements were also repeated for the three conditions with a 10 N lateral displacement force applied to the patella.ResultsReduction of VMM tension resulted in significant increases in lateral patellar tilt (2.8°) and translation (4 mm), with elevated lateral and reduced medial joint contact pressures from 0.48 to 0.14 MPa, and reduced patellar stability (all p < 0.05).ConclusionsThese findings provide basic scientific rationale to support the role of quadriceps strengthening to resist patellar lateral maltracking and rebalance the articular contact pressure away from the lateral facet in patients with normal patellofemoral joint anatomy.